Genetic divergence in young plants of guaraná and possibilities of breeding - Filho, Firmino José do Nascimento; Cruz, Cosme Damião; Garcia, Terezinha Batista (Pesquisa Agropecuaria Brasileira, 1992)
Thyrty six clones of «guaraná» (Paullinia cupana var. sorbilis H.B.K.) were studied at the nursery stage, with respect to 25 agronomic characters, to evaluate the possibilities of obtaining gains through selection for some of the characters analysed. Additionally the identification of progenitors to use in breeding programs was porsued as well as of the promising materials to be used in vegetative propagation. A significant genetic variability (Pe.0,01) was found among the clones. The genotypic determination coefficient was above 80% for the majority of the characters studied. The superiority of the clone 416 was highlighted both for the aerial part and roots. The clones 206, 222, 224, 225, 343 and 636 were the most divergent in relation to clone 416, being therefore recommended for biparental or multiple crossing among them. The clones 217 and 413 were the most similar to 416 so that they can provide uniform populations through vegetative propagation while avoiding that the genetic base be restricted to a single genotype.